DOMINASI MASKULINITAS PADA KARAKTER DAN PERAN KALUNA DALAM FILM HOME SWEET LOAN - Putri, Shalfa Zahra Amanda; Marta, Rustono Farady; Borges, Serilio Verdial Maria; Fernando, Joshua; Anggreni, Likha Sari (JURNAL KELUARGA SEHAT SEJAHTERA, 2025)
This study aims to identify and understand how Kaluna’s character in the film “Home Sweet Loan” reflects elements of masculinity and gender roles. Using Tzvetan Todorov’s narrative analysis, the study explores Kaluna’s journey through five stages. The results show that Kaluna depicts the flexibility and dynamics of gender roles with masculine traits such as courage, assertiveness, and independence. Eagly A.H. social role theory in the study changes the perception of women as weak figures. The film raises the issue of masculinity and women living in a patriarchal culture, influencing the audience’s perception of gender roles